Built‐in‐self‐test technique for diagnosis of delay faults in cluster‐based field programmable gate arrays. Issue 5 (1st September 2013) - Das, Nachiketa; Roy, Pranab; Rahaman, Hafizur
Abstract : The increased circuit complexity of field programmable gate array (FPGA) poses a major challenge in the testing of FPGAs. One of the test challenges is to detect the delay faults in high‐speed circuits. Built‐in‐self‐test (BIST) Technique is an ease solution compared with expensive automatic test equipment. In this work, a BIST structure is proposed to detect the delay faults in the various resources of the FPGA such as multiplier, digital signal processing (DSP) block, look‐up tables etc. and interconnects of FPGA. The authors have also proposed a full‐diagnosable BISTer structure that improves the testing efficiency of the logic BIST. The proposed BISTer structure can diagnose the faulty configurable logic block (CLB), when all the CLBs in the 2 × 3 BIST are faulty. The proposed scheme has been simulated in Xilinx Vertex FPGA, using ISE tool, Jbits3.0 API and XHWI (Xilinx HardWare Interface) and MATLAB7.0. The result shows significant improvement compared with earlier BIST methods.